Optimizing Sustainable Tourism Capacity in Tanjung Bira: A Real-Time Environmental Management Dashboard Approach - Sabran Laori; Vinny Corylitha Sarapang; Nurjannah Nurjannah; masri ridwan (Universitas Sebelas Maret, 2024)
Bulukumba Regency, a renowned tourism destination in South Sulawesi, faces critical challenges in managing tourist impact and preserving environmental quality. This study examines tourism dynamics in Tanjung Bira and evaluates the area’s carrying capacity to inform sustainable management strategies. Using secondary data from tourism records (2018–2022) and employing a carrying capacity analysis, we calculated three main capacities: Physical Carrying Capacity (PCC) at 341,504 tourists, Real Carrying Capacity (RCC) at 222,319 tourists after accounting for environmental factors, and Effective Carrying Capacity (ECC) at 80% with 28 active management staff out of the 35 required. Findings reveal a substantial rise in domestic tourism but a pronounced decline in foreign visitor numbers, emphasizing the need for effective, sustainable strategies to balance growth and preservation. Additionally, we propose a Real-Time Environmental Management Dashboard to optimize waste management in Tanjung Bira, aiming to reduce environmental impact and engage community stakeholders. The study highlights practical solutions for sustainable tourism in Bulukumba.